Reappraisal of the Javanese Bullfrog complex, Kaloula baleata (Müller, 1836) (Amphibia: Anura: Microhylidae), reveals a new species from Peninsular Malaysia - Chan, Kin Onn; Grismer, L. Lee; Brown, Rafe M. (Zootaxa, 2014)
A new species of Narrow-mouthed frog of the genus Kaloula is described from northern Peninsular Malaysia. Kaloula latidisca sp. nov. is genetically and morphologically most similar to K. baleata and K. indochinensis but differs from those and other congeners by the unique combination of the following characters: (1) adult males SVL 49.2–56.2 mm (x̅=53.5 ± 3.0; N=4); (2) finger tips expanded into large, transversely expanded discs (disc width 2.8–3.1 mm, x̅=3.0 ± 0.1); (3) inner metatarsal tubercle large, oval, distinctly raised, slightly shorter than first toe; (4) three subarticular tubercles on fourth toe; (5) toe webbing formula: I 1–2 II 1–3 III 2–3.5 IV 4–2 V; and (6) yellow to orange irregularly shaped patch on the axillary, inguinal and posterior region of thigh.